2011
DOI: 10.1007/jhep05(2011)089
|View full text |Cite
|
Sign up to set email alerts
|

BKM Lie superalgebras from counting twisted CHL dyons

Abstract: Following Sen, we study the counting of ('twisted') BPS states that contribute to twisted helicity trace indices in four-dimensional CHL models with N = 4 supersymmetry. The generating functions of half-BPS states, twisted as well as untwisted, are given in terms of multiplicative eta products with the Mathieu group, M 24 , playing an important role. These multiplicative eta products enable us to construct Siegel modular forms that count twisted quarter-BPS states.The square-roots of these Siegel modular forms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 54 publications
(195 reference statements)
2
75
0
Order By: Relevance
“…It is therefore natural to wonder about the corresponding physical interpretation of the twisted twining genera φ g,h . In the special case of a trivial twist g = e, it has been shown that for some elements h the twining genera φ e,h correspond to BPS-indices in CHL-orbifolds [6,[51][52][53]. We may therefore expect that the twisted twining genera φ g,h should be related to the counting of 'twisted dyons' in CHL-models.…”
Section: Open Problems and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore natural to wonder about the corresponding physical interpretation of the twisted twining genera φ g,h . In the special case of a trivial twist g = e, it has been shown that for some elements h the twining genera φ e,h correspond to BPS-indices in CHL-orbifolds [6,[51][52][53]. We may therefore expect that the twisted twining genera φ g,h should be related to the counting of 'twisted dyons' in CHL-models.…”
Section: Open Problems and Future Workmentioning
confidence: 99%
“…For some conjugacy classes [g] ∈ M 24 the associated second-quantized twining genera Φ g also give rise to denominator formulas of GKMs [56], which should presumably be identified with the wall-crossing algebras found in CHL-models [51,[57][58][59][60]. Although these observations are very suggestive, the precise role of the GKMs for Mathieu Moonshine remains to be understood.…”
Section: Open Problems and Future Workmentioning
confidence: 99%
“…These models have been a remarkable arena for testing string dualities and analyzing black hole microstates (see [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] for a sample of references). In the non-orbifold case the N = 4 theory has duality group SL(2, Z) × SO (6, 22; Z), where the first factor is the S-duality group which acts as a strong-weak duality on the coupling S, while the second factor is the T-duality group.…”
Section: Jhep12(2015)156mentioning
confidence: 99%
“…The role of the McKay-Thompson series is here played by the so called twining genera φ g (τ, z), which are weak Jacobi forms with respect to subgroups of SL(2, Z). In our previous work [53] (generalising the earlier results [18,54]), we defined a class of infinite-products, labelled by commuting pairs g, h of elements in M 24 : 19) where the first product runs over…”
Section: Connection With Moonshinementioning
confidence: 99%
“…1 Since the K3 surface plays a central role in mathematics and physics, this new observation 1 Relatedly, M24 has at the same time been connected to the counting functions of half BPS states in four dimensional N = 4 theories [2,7,8].…”
Section: Introductionmentioning
confidence: 99%